(untitled) (Archives of Criminology, 2023)
The article presents efforts of foreign victims of trafficking in human beings who are trying to overcome the effects of their victimisation in Poland. The text aims to familiarise the audience with all aspects related to victimisation as a result of trafficking in human beings and to draw attention to the barriers to effective integration that victims face. The article presents research conducted on the basis of interviews with foreign victims – beneficiaries of the La Strada Foundation against Trafficking in Persons and Slavery in 2019. The barriers to effective integration are shown from two perspectives. Firstly, the text presents the personal difficulties of victims of trafficking in human beings, resulting from their personal experiences, such as trauma, a sense of loneliness and alienation, a fear of being discriminated against, the need to keep a family in the country of origin, or unfamiliarity with the language. The article also explores institutional barriers, independent of the disposition of the victims, which can lead to their secondary victimisation, such as the attitude of law enforcement agencies, a complicated legalisation procedure, or a harmful form of media coverage.